2020
DOI: 10.3390/ijms21031024
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the CRISPR Toolbox in P. patens Using SpCas9-NG Variant and Application for Gene and Base Editing in Solanaceae Crops

Abstract: Genome editing has become a major tool for both functional studies and plant breeding in several species. Besides generating knockouts through the classical CRISPR-Cas9 system, recent development of CRISPR base editing holds great and exciting opportunities for the production of gain-of-function mutants. The PAM requirement is a strong limitation for CRISPR technologies such as base editing, because the base substitution mainly occurs in a small edition window. As precise single amino-acid substitution can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…Here, we show for the first time that PPE2 strategy developed for dicot species is able to edit an endogenous gene in the cultivated tetraploid potato. Compared to our previous work on cytosine base editing in potato and Arabidopsis (Bastet et al, 2019;Veillet et al, 2019b;Veillet et al, 2019a;Veillet et al, 2020), the efficiency of our PPE strategy appears to be limited, as already observed for cereals. Once improved, the prime editing technology, by largely expanding the range of targeted base substitutions, could make precision breeding amenable in polyploid and vegetatively propagated crops such as potato.…”
Section: Resultsmentioning
confidence: 65%
“…Here, we show for the first time that PPE2 strategy developed for dicot species is able to edit an endogenous gene in the cultivated tetraploid potato. Compared to our previous work on cytosine base editing in potato and Arabidopsis (Bastet et al, 2019;Veillet et al, 2019b;Veillet et al, 2019a;Veillet et al, 2020), the efficiency of our PPE strategy appears to be limited, as already observed for cereals. Once improved, the prime editing technology, by largely expanding the range of targeted base substitutions, could make precision breeding amenable in polyploid and vegetatively propagated crops such as potato.…”
Section: Resultsmentioning
confidence: 65%
“…The PCR fragment was cloned into an intermediate pTwist plasmid through Mlu I/ Eco RI restriction followed by T4 DNA ligation (ThermoFisher Scientific, USA). A sequence encoding the PmCDA1 and UGI catalytic domains was previously dicot-codon optimized and synthesized (TwistBioscience, USA) [ 21 ], and cloned into the intermediate pTwist plasmid through EcoR I restriction and T4 DNA ligation (ThermoFisher Scientific, USA), downstream of the SanCas9 coding sequence. The construct was checked by sanger sequencing ( S1 Table ).…”
Section: Methodsmentioning
confidence: 99%
“…We first introduced a point mutation in the SaCas9 sequence to produce a SanCas9 (D10A) that we fused to a dicot codon-optimized fragment consisting in a cytosine deaminase (PmCDA1) and an uracil glycosylase inhibitor (UGI) domain. This fusion protein was cloned into a modified version of the pDe backbone [21,27,28], resulting in the pDeSanCas9_PmCDA1_UGI binary vector for expression in dicot species (Fig 3A). The four sgRNAs used for CRISPR-mediated indels were individually cloned into this CBE through Gateway cloning (Fig 3B), each spacer harboring two to five cytosines in the putative editing window (distal part of the spacer sequence from the PAM) for this CBE, based on previous studies using the PmCDA1 enzyme in plants with SpnCas9 or SanCas9 [15,19,21,29,30] ( Fig 3B).…”
Section: Crispr-sancas9-mediated Cytosine Base Editing Of the Potatomentioning
confidence: 99%
See 1 more Smart Citation
“…The xCas9 variant of SpCas9 could target NG, GAA, and GAT PAMs, which successfully expanded the scope of genome editing in rice [59,60]. In plants and human cells, SpCas9-NG variant was successfully tested that recognizes the NGN PAM [61][62][63][64]. Veillet et al [63] compared the efficiency of xCas9, SpCas9, and SpCas9-NG and found SpCas9-NG targets more efficiently alternative NGT PAMs in plants.…”
Section: Evolution Of Base Editorsmentioning
confidence: 99%